Dextran or Saline Can Replace Contrast for Intravascular Optical Coherence Tomography in Lower Extremity Arteries. (October 2016) - Kendrick, Daniel E.; Allemang, Matthew T.; Gosling, Andre F.; Nagavalli, Anil; Kim, Ann H.; Nishino, Setsu; Parikh, Sahil A.; Bezerra, Hiram G.; Kashyap, Vikram S.
Purpose: To examine the hypothesis that alternative flush media could be used for lower extremity optical coherence tomography (OCT) imaging in long lesions that would normally require excessive use of contrast.Methods: The OPTical Imaging Measurement of Intravascular Solution Efficacy (OPTIMISE) trial was a single-center, prospective study ( ClinicalTrials.gov identifier NCT01743872) that enrolled 23 patients (mean age 68±11 years; 14 men) undergoing endovascular intervention involving the superficial femoral artery. Four flush media (heparinized saline, dextran, carbon dioxide, and contrast) were used in succession in random order for each image pullback. Quality was defined as ≥270° visualization of vessel wall layers from each axial image. Mean proportions (± standard deviation) of image quality for each flush medium were assessed using 1-way analysis of variance and are reported with the 95% confidence intervals (CI).Results: Four OCT catheters failed, leaving 19 patients who completed the OCT imaging protocol; from this cohort, 51 highest quality runs were selected for analysis. Average vessel diameter was 3.99±1.01 mm. OCT imaging allowed 10- to 15-μm resolution of the lumen border, with diminishing quality as vessel diameter increased. Plaque characterization revealed fibrotic lesions. Mean proportions of image quality were dextran 87.2%±12% (95% CI 0.81 to 0.94), heparinized saline 74.3%±24.8% (95% CI 0.66 to 0.93), contrast 70.1%±30.5% (95% CI 0.52 to 0.88), and carbon dioxide 10.0%±10.4% (95% CI 0.00 to 0.26). Dextran, saline, and contrast provided better quality than carbon dioxide (p<0.001).Conclusion: OCT is feasible in peripheral vessels <5 mm in diameter. Dextran or saline flush media can allow lesion characterization, avoiding iodinated contrast. Carbon dioxide is inadequate for peripheral OCT imaging. Axial imaging may aid in enhancing durability of peripheral endovascular interventions.